Evaluation of companies (Magazine Luiza SA) and investments in the E-commerce area during the Covid-19 pandemic period - Carvalho, Cleginaldo; Miki Ishikura, Larissa; Braga Silva, Iris; Marinho Arruda, Matheus; Luciene Garcia dos Santos, Tainá; Godoi Cutait, Rafael (Technium Social Sciences Journal, 2023)
In view of the economic impact and the changes in life habits caused by the Covid-19 pandemic in Brazil, the main objective of this article refers to the application of the fundamentalist valuation method of companies, called discounted cash flow, during the beginning, the course and the end of the pandemic period. The company in question is Magazine Luiza SA, given the positive variation in the value of the company's shares during this interval, as well as the investments made in digital transformation and the consequent significant increase in sales. The methodology adopted consists of collecting data disclosed by the company itself and, through the application of FCFF, performing the company's evaluation during the years 2019 to 2022, which characterized the duration of the pandemic, in addition to performing a projection based on the analysis performed until the year 2028. The analysis obtained showed slow and steady growth in the pre-pandemic period, that the initial pandemic period, between the years 2019 and 2020 represented for Magazine Luiza, contrary to what is expected for a retail company, a period of accelerated growth, which can be associated with the investments made for the digital transformation. Moreover, the projection obtained indicates, for the company, an initial crisis in the post-pandemic period, given the current political-economic environment. However, it presents trends for a recovery followed by subsequent accelerated growth.